Tensor-Based Methods for Blind Spatial Signature Estimation in Multidimensional Sensor Arrays - Paulo R. B. Gomes; André L. F. de Almeida; João Paulo C. L. da Costa; João C. M. Mota; Daniel Valle de Lima; Giovanni Del Galdo (International Journal of Antennas and Propagation)
The estimation of spatial signatures and spatial frequencies is crucial for several practical applications such as radar, sonar, and wireless communications. In this paper, we propose two generalized iterative estimation algorithms to the case in which a multidimensional (R-D) sensor array is used at the receiver. The first tensor-based algorithm is an R-D blind spatial signature estimator that operates in scenarios where the source’s covariance matrix is nondiagonal and unknown. The second tensor-based algorithm is formulated for the case in which the sources are uncorrelated and exploits the dual-symmetry of the covariance tensor. Additionally, a new tensor-based formulation is proposed for an L-shaped array configuration. Simulation results show that our proposed schemes outperform the state-of-the-art matrix-based and tensor-based techniques.